Analysis of Causal Nexus between Defense Spending and Economic Growth in Nigeria: A Toda-Yamamoto Approach - Eromosele, Ofino, Emmanuel; Adele, Orisadare Monica (The Economics and Finance Letters, 2020)
The research analysed the causal nexus between defense spending and growth in Nigeria. These were done with the aim to ascertain the causality direction between spending in defense sector and growth in Nigeria. Annual data from secondary sources spanning from 1980- 2017 were employed for the study. Defense spending data was gotten from the Statistical Bulletin of the Central Bank of Nigeria (CBN), whereas real Gross Domestic Product (RGDP) was gotten from World Bank Development Indicator (WDI). Toda-Yamamoto (TY) causality method was used to ascertain the causality direction between defense spending and economic growth. Lastly, empirical results using Toda-Yamamoto (TY) technique showed that there was no direction of causality between defense spending and economic growth within the research period since the probability value of LTOMILEX (0.38) and LRGDP (0.22) were higher than 0.05 level of significance. This denotes that defense spending did not granger cause economic growth and vis-a-ditto within the study. Therefore, the paper concluded that no direction of causality exist between defense spending and economic growth in Nigeria within the span of study.